The struggle against corporate encroachment in Indian agriculture. (June 2022) - Kaur, Navpreet; Saratchand, C.
The repeal of the Three Farm Laws by the Union Government of India is the first consequential setback to the neoliberal project in India after 2014. The struggle was largely carried out by peasants in alliance with workers. The Left in India played a decisive role in crafting this setback to the neoliberal project by working towards the building of a tendential working alliance between peasants and workers. The popular resistance that has been engendered by the upsurge of peasants and workers will need to nurture this alliance, renew its focus on combatting gender and caste oppression, and engage in an authentic effort to build solidarity among the various constituents of the democratic movement in India.